N-doped graphene coated silicon-based negative electrode material and preparation method thereof

Through the preparation method of N-doped graphene-coated silicon-based negative electrode material, the stress problem caused by volume changes in the silicon negative electrode material during charging and discharging is solved, and efficient electrochemical performance improvement and material stability enhancement is achieved.

CN119627069APending Publication Date: 2025-03-14INNER MONGOLIA SHANSHAN TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411721032.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Volume changes in silicon negative electrode materials during charging and discharging lead to stress, resulting in material cracking, powdering and electrochemical performance degradation. Especially in densely stacked electrode environments, the critical size of the silicon negative electrode materials is small and the lithium ion diffusion rate is low.

Method used

The preparation method of N-doped graphene-coated silicon-based negative electrode material is adopted, and the coating of graphene and micro-nanoization of silicon-based materials are achieved through the mixing of nanosilicon and nanosilicon dioxide, the addition of modified powder, the in-situ sealing reaction of vacuum high-temperature furnaces, the peeling and spray drying of high-speed sand mills.

Benefits of technology

It effectively protects electroactive substances from volume changes, improves electrochemical properties and material stability, extends recycling life, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627069A_ABST
    Figure CN119627069A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an N-doped graphene-coated silicon-based negative electrode material, which comprises the following steps of: performing carbon coating by using graphene, controlling the particle size of a silicon substrate to be less than 2 microns, and realizing micro-nanocrystallization of a silicon main body material through mechanical ball milling, so that the micro-nanocrystallization silicon material is distributed in a graphite layer while metal-doped silicon monoxide obtains a smaller particle size; according to the preparation method, metal doped silicon monoxide is taken as a silicon source, the surface of the metal doped silicon monoxide is coated with the stripped graphene, the metal doped silicon monoxide is coated with the graphene oxide, finally, a silicon material is further uniformly coated with graphene micro-nanosheets by adopting a rapid spray drying technology, and an electroactive substance is effectively protected from being influenced by volume change caused in the charging and discharging process through the synergistic effect of the graphene micro-nanosheets. The preparation method has the advantages that after the composite material is prepared from micron-sized silicon monoxide and graphene, low-cost preparation of the modified silicon monoxide is realized, the electrode material with excellent electrochemical performance is obtained, the stability of the composite material is effectively improved, the cycle service life is prolonged, and the application and popularization value is relatively good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The present invention relates to the technical field of negative electrode material preparation, and in particular to an N-doped graphene-coated silicon-based negative electrode material and a preparation method thereof. Background technology:

[0002] Silicon negative electrode materials undergo large volume changes during the alloying and dealloying stages of lithium and silicon during the charge and discharge process. The stress generated can cause cracking or even pulverization of the silicon negative electrode, the separation of the active material from the current collector, and ultimately the attenuation of capacity. Considering that in actual applications, in the case of densely stacked real electrodes, due to the additional interaction force exerted by the expansion of adjacent particles, the critical size of the silicon negative electrode material in a volume-constrained environment may be much smaller than the size observed in an unconstrained environment, and the relatively low diffusion rate of lithium ions in silicon (extremely low conductivity) affects the electrochemical performance. The volume change of silicon monoxide (SiO) is smaller than that of pure silicon, and it is easy to produce, which means that SiO is a negative electrode material for future promotion and application. At present, the volume expansion is alleviated as much as possible by controlling the reduction of the material particle size, but the industry generally controls the particle size at around 5μm, and the cost of carbon coating on the surface by gas phase coating is high, which seriously restricts the development of the industry. Summary of the invention:

[0003] In order to solve the above problems, the first object of the present invention is to provide a method for preparing an N-doped graphene-coated silicon-based negative electrode material, and the second object of the present invention is to provide an N-doped graphene-coated silicon-based negative electrode material.

[0004] The first object of the present invention is implemented by the following technical solutions:

[0005] A method for preparing an N-doped graphene-coated silicon-based negative electrode material comprises the following steps:

[0006] (1) selecting nano-silicon solution, nano-silicon dioxide sol, modified powder, dispersant and N-doped graphene coating agent;

[0007] (2) mixing the nano-silicon solution selected in step (1) with the nano-silicon dioxide sol, filtering and drying under positive pressure to obtain a mixed powder 1; or filtering and drying the nano-silicon solution and the nano-silicon dioxide sol under positive pressure to obtain a nano-silicon dry powder and a nano-silicon dioxide dry powder, respectively, and then mixing the nano-silicon dry powder and the nano-silicon dioxide dry powder to obtain a mixed powder 1;

[0008] In the mixed powder 1, the mass ratio of nano silicon dry powder to nano silicon dioxide dry powder is 1:2;

[0009] (3) uniformly mixing the mixed powder 1 obtained in step (2) and the modified powder in a mass ratio of 20:(1-3), performing an in-situ closed reaction in a vacuum high-temperature furnace, and then crushing the mixture to obtain a precursor material;

[0010] (4) adding the precursor material and the dispersant obtained in step (3) into an organic solution, wherein the mass ratio of the precursor material, the dispersant, and the organic solution is 1:0.1:10-20, and stirring evenly to obtain a dispersion 1;

[0011] (5) mixing the dispersion 1 obtained in step (4) with the N-doped graphene capping agent in a mass ratio of 1:1, and exfoliating the solute using a high-speed sand mill to obtain a dispersion 2;

[0012] (6) The dispersion 2 obtained in step (5) is spray-dried to obtain an N-doped graphene-coated silicon-based negative electrode material.

[0013] Furthermore, the method for preparing the nano-silicon solution comprises the following steps:

[0014] (11) The silicon source, the reducing agent, and the solvent are mixed uniformly in a mass ratio of 5:1:20, and the mixed solution is placed in a digestion tank, and a protective gas is introduced into the digestion tank, and the pressure is maintained at 0.5 to 3.5 MPa; the digestion tank is placed in a microwave digestion instrument, the microwave power is controlled at 500 W to 1000 W, the temperature is controlled at 80° C. to 200° C., and the reaction is carried out for 0.05 h to 5 h, and then the reaction solution is obtained;

[0015] (12) dialyzing and precipitating the reaction solution obtained in step (11) to remove unreacted impurities and by-products to obtain a nano-silicon solution;

[0016] In step (11), the silicon source is any one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, methyltrimethoxysilane, methyldiethoxysilane and triethoxysilane;

[0017] The reducing agent is any one of trisodium citrate, citric acid, hydrazine hydrate, acetaldehyde, sodium oxalate, oxalic acid, VC, and OA;

[0018] The solvent is any one of water, anhydrous ethanol and N,N-dimethylformamide;

[0019] The protective gas includes inert gases such as argon and nitrogen.

[0020] Furthermore, the preparation method of the nano silica sol comprises the following steps:

[0021] In parts by weight, 10 parts of ammonia water with a mass fraction of 25-35% are added to 1200-1250 parts of ethanol with a mass fraction of 91-94%, and then 100-120 parts of tetraethyl orthosilicate are added dropwise, and the mixture is reacted for 2-18 hours at 50°C-70°C and 500-800 r / min stirring conditions. After the reaction is completed, the mixture is washed by centrifugation with ethanol, and after centrifugation, the substrate is added to a solvent for dispersion to obtain a nano-silica sol.

[0022] Furthermore, the modified powder includes one or more powders of Al, Na, Li, Mg, Ca, Ti, Mn, Co, Ni, Cu, Zn, Zr, Mo, Ge, and Sn.

[0023] Furthermore, the dispersant is one of triethylhexyl phosphate, sodium lauryl sulfate, cellulose derivatives, organic solvents such as NMP, alcohols, etc.

[0024] Furthermore, the preparation method of the N-doped graphene coating agent comprises the following steps:

[0025] (51) preparing a nitrogen source and graphite oxide in a mass ratio of (0.8-1.5):1, adding water to prepare an aqueous solution with a mass fraction of graphite oxide of 0.5%-5%; preliminarily dispersing the aqueous solution in an ultrasonic cleaning machine to obtain a dispersion A;

[0026] (52) The dispersion A obtained in step (51) is transferred to a high-pressure reactor for hydrothermal reaction at a temperature of 100-300° C. and a reaction time of 5 to 20 hours to obtain an N-doped graphene encapsulant.

[0027] Furthermore, in step (3), the vacuum high temperature furnace is used for in-situ closed reaction, the temperature is 850-1350° C., the vacuum value is less than 1 Pa, and the insulation time is 1-25 h;

[0028] The particle size D50 of the precursor material is 1-2 μm.

[0029] Furthermore, in step (5), the process conditions of the high-speed sand mill are: motor power 3.2 to 4 kW.

[0030] Furthermore, in step (6), the process conditions for spray drying are: the inlet air temperature of the spray drying tower is 230-270°C, the outlet air temperature is 130-180°C, and the air flow is 2-8m 3 / min. Under this condition, a negative electrode material with higher tap density, tighter structure and more stability was obtained.

[0031] The second object of the present invention is implemented by the following technical solutions:

[0032] A method for preparing an N-doped graphene-coated silicon-based negative electrode material obtains an N-doped graphene-coated silicon-based negative electrode material.

[0033] Advantages of the present invention:

[0034] The present invention uses graphene for carbon coating, controls the silicon-based particle size to be below 2 μm, and realizes micro-nano silicon main material through mechanical ball milling, so that metal-doped silicon monoxide obtains a smaller particle size, while the micro-nano silicon material is distributed in the graphite layer, and the peeled graphene is coated on its surface, so that the metal-doped silicon monoxide is coated by graphene oxide, and finally the rapid spray drying technology is used to further uniformly wrap the silicon material through the graphene micro-nano sheet, and the synergistic effect effectively protects the electroactive material from the volume change caused by the charging and discharging process. Due to the interesting structural and morphological characteristics produced by the cage effect of the detached graphene sheet, these 3D / 2D composite microspheres are expected to be used as negative electrode materials for high-performance lithium-ion batteries.

[0035] The present invention adopts micron-sized silicon oxide and graphene to prepare the composite material, which not only realizes the low-cost preparation of modified silicon oxide and obtains electrode materials with excellent electrochemical properties, but also effectively improves the stability of the composite material and increases the cycle life, thus having good application and promotion value. Description of the drawings:

[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0037] Figure 1 SEM of N-doped graphene coated silicon-based negative electrode material Figure 1 ;

[0038] Figure 2 SEM of N-doped graphene coated silicon-based negative electrode material Figure 2 ;

[0039] Figure 3 This is the XRD pattern of N-doped graphene-coated silicon-based negative electrode material;

[0040] Figure 4 This is the charge and discharge curve of N-doped graphene-coated silicon-based negative electrode material. Specific implementation method:

[0041] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] Embodiment 1:

[0043] like Figure 1-4 A method for preparing an N-doped graphene-coated silicon-based negative electrode material is shown, comprising the following steps:

[0044] (1) selecting nano-silicon solution, nano-silicon dioxide sol, modified powder, dispersant and N-doped graphene coating agent;

[0045] (2) mixing the nano-silicon solution selected in step (1) with the nano-silicon dioxide sol, filtering and drying under positive pressure to obtain a mixed powder 1; or filtering and drying the nano-silicon solution and the nano-silicon dioxide sol under positive pressure to obtain nano-silicon dry powder and nano-silicon dioxide dry powder, respectively, and then mixing the nano-silicon dry powder and the nano-silicon dioxide dry powder to obtain a mixed powder 1;

[0046] In the mixed powder 1, the mass ratio of nano silicon dry powder to nano silicon dioxide dry powder is 1:2;

[0047] (3) The mixed powder 1 obtained in step (2) and the modified powder are uniformly mixed in a mass ratio of 20:1, and the mixture is crushed after an in-situ closed reaction in a vacuum high-temperature furnace to obtain a precursor material; the in-situ closed reaction in a vacuum high-temperature furnace is carried out at a temperature of 1250° C., a vacuum value of <1 Pa, and a holding time of 15 h; the particle size D50 of the precursor material is 1.5 μm.

[0048] Si, SiO2 react with modified powder to generate silicon monoxide (SiO) as the matrix, and silicon (Si) and inert MzSiyOx compounds are precipitated in the intermediate phase. The inert MzSiyOx compounds reduce active oxygen and can effectively improve the initial performance of the negative electrode material.

[0049] (4) adding the precursor material and dispersant obtained in step (3) to the organic solution, wherein the mass ratio of the precursor material: the dispersant: the organic solution is 1:0.1:10, and stirring evenly to obtain a dispersion 1;

[0050] (5) The dispersion 1 obtained in step (4) is mixed with the N-doped graphene encapsulating agent in a mass ratio of 1:1, and the solute is stripped by a high-speed sand mill to obtain a dispersion 2; the process conditions of the high-speed sand mill are: motor power 3.5 kW.

[0051] Graphite oxide is used as the raw material. The large distance between graphite layers is beneficial to the insertion of silicon-based materials into the graphite layer. At the same time, the outer layer is easy to peel off into graphene. Under surface tension, graphene can easily cover the free silicon-based materials that have not entered the graphene layer on the surface of the substrate; N-doped graphene coating agent coating, regulating the N doping type and doping amount, significantly improves the performance of graphene and adds new active sites under the condition of low N atom doping amount, and forms a mesh conductive network and its buffer layer architecture with the internal graphene, which has a promoting effect on the fast charging performance of graphene-coated high-first-effect metal-doped silicon-based negative electrode materials;

[0052] The graphite oxide is exfoliated into graphene by a high-speed sand mill to realize micro-nanoization of the silicon main material, so that the metal-doped silicon monoxide has a smaller particle size, while the micro-nano silicon material is distributed in the graphite layer, and the exfoliated graphene is coated on its surface, so that the metal-doped silicon monoxide is coated by the graphene oxide, and an N-doped pomegranate-shaped mesh graphene conductive network is obtained;

[0053] (6) The dispersion 2 obtained in step (5) is spray dried to obtain the N-doped graphene-coated silicon-based negative electrode material. The spray drying process conditions are: the spray drying tower inlet air temperature is 240°C, the outlet air temperature is 170°C, and the air flow is 5m 3 / min.

[0054] (7) By spray drying, the dispersion 2 is obtained into dry powder. At the same time, the spraying process optimizes the N-doped pomegranate-type mesh graphene conductive network structure obtained in step (5), and the graphene is more tightly combined with the silicon-based main material, and the conductivity is enhanced. The structure constructed by graphene can effectively alleviate the volume expansion caused by the electrochemical reaction.

[0055] In this embodiment, the preparation method of the nano-silicon solution includes the following steps:

[0056] (11) The silicon source, the reducing agent, and the solvent are mixed uniformly in a mass ratio of 5:1:20, and the mixed solution is placed in a digestion tank, and a protective gas is introduced into the digestion tank, and the pressure is maintained at 2 MPa; the digestion tank is placed in a microwave digestion instrument, the microwave power is controlled at 800 W, the temperature is controlled at 150° C., and the reaction is carried out for 2 hours to obtain a reaction solution;

[0057] (12) dialyzing and precipitating the reaction solution obtained in step (11) to remove unreacted impurities and by-products to obtain a nano-silicon solution;

[0058] In step (11), the silicon source is 3-aminopropyltrimethoxysilane; the reducing agent is hydrazine hydrate; the solvent is N,N-dimethylformamide; and the protective gas is argon inert gas.

[0059] The preparation method of nano silica sol comprises the following steps:

[0060] By weight, 10 parts of 30% ammonia water were added to 1200 parts of 92% ethanol, and then 100 parts of tetraethyl orthosilicate were added dropwise. The mixture was reacted at 60°C and 600 r / min for 10 hours. After the reaction, the mixture was washed by centrifugation with ethanol. After centrifugation, the substrate was added to a solvent for dispersion to obtain a nano-silica sol.

[0061] The modified powder is Mg powder and the dispersant is carboxymethyl cellulose.

[0062] The preparation method of the N-doped graphene coating agent comprises the following steps:

[0063] (51) After the N source and graphite oxide were prepared in a mass ratio of 1:1, water was added to prepare an aqueous solution with a mass fraction of graphite oxide of 5%; the aqueous solution was preliminarily dispersed by an ultrasonic cleaning machine (ultrasonic 800W, time 2h) to obtain a dispersion A;

[0064] (52) The dispersion A obtained in step (51) is transferred to a high-pressure reactor for hydrothermal reaction. After a reaction time of 10 hours at a temperature of 180° C., an N-doped graphene encapsulant is obtained.

[0065] Embodiment 2:

[0066] The only difference between this embodiment and Embodiment 1 is that the particle size D50 of the precursor material is 1 μm.

[0067] Embodiment 3:

[0068] The only difference between this embodiment and embodiment 1 is that in step (42), the obtained dispersion A is transferred to a high-pressure reactor for hydrothermal reaction, and an N-doped graphene encapsulant is obtained after a reaction time of 20 hours at a temperature of 250°C.

[0069] Embodiment 4:

[0070] The difference between this embodiment and embodiment 1 is that the spray drying tower inlet air temperature is 240°C, the outlet air temperature is 180°C, and the air flow is 8m 3 / min.

[0071] Comparative Example 1:

[0072] The only difference between this embodiment and embodiment 1 is that the 3 μm precursor material is directly mixed with the N-doped graphene covering agent in a mass ratio of 1:1, and spray drying is performed directly without passing through a sand mill.

[0073] Comparative Example 2:

[0074] The difference between this embodiment and embodiment 1 is that step (52) is removed: the dispersion A obtained in step (51) is not subjected to a hydrothermal reaction, and the N-doped graphene operation is not performed, but is directly mixed with the dispersion 1 in a mass ratio of 1:1, and subsequent operations are performed.

[0075] Comparative Example 3:

[0076] The only difference between this embodiment and embodiment 1 is that spray drying is not performed, and the dispersion 2 obtained in step (5) is subjected to high-pressure filtration and freeze drying.

[0077] Embodiment 5:

[0078] The N-doped graphene-coated silicon-based negative electrode materials obtained in Examples 1-4 and Comparative Examples 1-3 were made into button batteries, and the electrochemical performance of each battery was tested. The production method is as follows:

[0079] The negative electrode material, conductive agent (A+B), binder and water are mixed in a weight ratio of 70:15:5:10 to form a uniform slurry, which is coated on the current collector copper foil and pressed to obtain a working electrode. The copper foil coated with the sample is placed in a vacuum drying oven, and the sample is taken out after drying. The electrode sheet is punched and placed in a mikaelona glove box. The metal lithium sheet is used as the counter electrode, the electrolyte is 1MLiPFB6B DMC+EMC+EC (1:1:1), and the CELGARD separator is assembled into a CR2430 button cell. The test procedure is:

[0080] Discharge rate: 0.1C; cut-off voltage: 10mV; standstill: 10min;

[0081] Discharge rate: 0.02C; cut-off voltage: 5mV; standstill: 10min;

[0082] Charging rate: 0.1C; cut-off voltage: 1.5V.

[0083] The electrochemical performance test results are shown in Table 1.

[0084] Table 1 Electrochemical performance test results

[0085]

[0086]

[0087] It can be seen from Table 1 that the expansion and cracking of silicon particles is often related to the size of the particles. Generally speaking, the cracking of larger μm-level silicon particles is more serious, while nano-level particles with a size less than a certain critical value will have fewer cracks. The best way to utilize μm-level particles in the present invention is to compound them with graphene. By comparing Example 2 with Example 1, the silicon-based material is reduced in size, the resistivity is reduced, and the capacity retention rate of 10 weeks of charge and discharge cycles is improved. Compared with Comparative Example 1, without a sand mill, the capacity retention rate is reduced to 84.67%; Example 3 increases the temperature and time of N-doped graphene, the active sites of graphene increase, and the capacity retention rate can reach 88.51%. Compared with Comparative Example 2, N-doped graphene is not used, the active sites are reduced, resulting in the deterioration of the overall performance of the mixed material, and the capacity retention rate is 85.92%. In Example 4, the spray temperature increases, the graphene coating becomes tighter, the coating effect is better, and a tight electronic conduction network is formed. Compared with Example 1, the resistivity is reduced by 0.33Ω.Cm, and the capacity retention rate is increased to 88.32%. In summary, the present invention improves the electrochemical performance by coating the modified silicon-based material with surface N-doped graphene: the carbon layer provides an elastic shell and reduces the volume change during the alloying / de-alloying process; the spray drying forms a dense surface to reduce the side reaction between the active substance and the electrolyte; the three-dimensional graphene network structure provides a large number of lithium ion and electron transmission channels, thereby improving the applicability of silicon-oxygen materials. After the composite material is prepared by using micron-level silicon oxide and graphene together, not only the low-cost preparation of modified silicon oxide is achieved, and the electrode material with excellent electrochemical performance is obtained, but also the stability of the composite material is effectively improved, and the cycle life is increased.

[0088] pass Figure 1 , Figure 2 The SEM image of the N-doped graphene-coated silicon-based negative electrode material shown in the figure shows that micro-nano silicon is dispersed in the graphene, the three-dimensional graphene wraps the micro-nano silicon, and the graphene has a mesh-like conductive network. Figure 3 The XRD pattern of the N-doped graphene-coated silicon-based negative electrode material shown in the figure shows that there are obvious silicon characteristic peaks and graphene characteristic peaks. The silicon-oxygen precursor was successfully prepared, and a magnesium silicate peak appeared at 30-25°, which removed the active oxygen of silicon-oxygen and formed inert substances, thereby improving the cycle. Figure 4 From the charge and discharge curve of the N-doped graphene-coated silicon-based negative electrode material shown in the figure, it can be seen that after the negative electrode material of Example 3 was assembled and charged, a charge and discharge test was performed using a blue battery. The first lithium insertion capacity was 1705.06 mAh / g, the lithium removal capacity was 1415.2 mAh / g, and the first efficiency was 83%. It can be used as a negative electrode material for lithium batteries, and its 10 cycle capacity retention rate is 88.51%.

[0089] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an N-doped graphene-coated silicon-based negative electrode material, characterized in that: The following steps are involved: (1) selecting nano-silicon solution, nano-silicon dioxide sol, modified powder, dispersant and N-doped graphene coating agent; (2) mixing the nano-silicon solution selected in step (1) with the nano-silicon dioxide sol, filtering and drying under positive pressure to obtain a mixed powder 1; or filtering and drying the nano-silicon solution and the nano-silicon dioxide sol under positive pressure to obtain a nano-silicon dry powder and a nano-silicon dioxide dry powder, respectively, and then mixing the nano-silicon dry powder and the nano-silicon dioxide dry powder to obtain a mixed powder 1; In the mixed powder 1, the mass ratio of nano silicon dry powder to nano silicon dioxide dry powder is 1:2; (3) uniformly mixing the mixed powder 1 obtained in step (2) and the modified powder in a mass ratio of 20:(1-3), performing an in-situ closed reaction in a vacuum high-temperature furnace, and then crushing the mixture to obtain a precursor material; (4) adding the precursor material and the dispersant obtained in step (3) into an organic solution, wherein the mass ratio of the precursor material, the dispersant, and the organic solution is 1:0.1:10-20, and stirring evenly to obtain a dispersion 1; (5) mixing the dispersion 1 obtained in step (4) with the N-doped graphene capping agent in a mass ratio of 1:1, and exfoliating the solute using a high-speed sand mill to obtain a dispersion 2; (6) The dispersion 2 obtained in step (5) is spray-dried to obtain an N-doped graphene-coated silicon-based negative electrode material.

2. The method for preparing an N-doped graphene-coated silicon-based negative electrode material according to claim 1, characterized in that: The preparation method of the nano-silicon solution comprises the following steps: (11) The silicon source, the reducing agent, and the solvent are mixed uniformly in a mass ratio of 5:1:20, and the mixed solution is placed in a digestion tank, and a protective gas is introduced into the digestion tank, and the pressure is maintained at 0.5 to 3.5 MPa; the digestion tank is placed in a microwave digestion instrument, the microwave power is controlled at 500 W to 1000 W, the temperature is controlled at 80° C. to 200° C., and the reaction is carried out for 0.05 h to 5 h, and then the reaction solution is obtained; (12) dialyzing and precipitating the reaction solution obtained in step (11) to remove unreacted impurities and by-products to obtain a nano-silicon solution; In step (11), the silicon source is any one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, methyltrimethoxysilane, methyldiethoxysilane and triethoxysilane; The reducing agent is any one of trisodium citrate, citric acid, hydrazine hydrate, acetaldehyde, sodium oxalate, oxalic acid, VC, and OA; The solvent is any one of water, anhydrous ethanol and N,N-dimethylformamide; The protective gas includes inert gases such as argon and nitrogen.

3. The method for preparing an N-doped graphene-coated silicon-based negative electrode material according to claim 1, characterized in that: The preparation method of the nano silica sol comprises the following steps: In parts by weight, 10 parts of ammonia water with a mass fraction of 25-35% are added to 1200-1250 parts of ethanol with a mass fraction of 91-94%, and then 100-120 parts of tetraethyl orthosilicate are added dropwise, and the mixture is reacted for 2-18 hours at 50°C-70°C and 500-800 r / min stirring conditions. After the reaction is completed, the mixture is washed by centrifugation with ethanol, and after centrifugation, the substrate is added to a solvent for dispersion to obtain a nano-silica sol.

4. The method for preparing an N-doped graphene-coated silicon-based negative electrode material according to claim 1, characterized in that: The modified powder includes one or more powders of Al, Na, Li, Mg, Ca, Ti, Mn, Co, Ni, Cu, Zn, Zr, Mo, Ge, and Sn.

5. The method for preparing an N-doped graphene-coated silicon-based negative electrode material according to claim 1, characterized in that: The dispersant is one of triethylhexyl phosphoric acid, sodium lauryl sulfate and cellulose derivatives.

6. The method for preparing an N-doped graphene-coated silicon-based negative electrode material according to claim 1, characterized in that: The preparation method of the N-doped graphene coating agent comprises the following steps: (51) preparing a nitrogen source and graphite oxide in a mass ratio of (0.8-1.5):1, adding water to prepare an aqueous solution with a mass fraction of graphite oxide of 0.5%-5%; preliminarily dispersing the aqueous solution in an ultrasonic cleaning machine to obtain a dispersion A; (52) The dispersion A obtained in step (51) is transferred to a high-pressure reactor for hydrothermal reaction at a temperature of 100-300° C. and a reaction time of 5 to 20 hours to obtain an N-doped graphene encapsulant.

7. The method for preparing an N-doped graphene-coated silicon-based negative electrode material according to claim 1, characterized in that: In step (3), the vacuum high temperature furnace is used for in-situ closed reaction, the temperature is 850-1350° C., the vacuum value is less than 1 Pa, and the insulation time is 1-25 h; The particle size D50 of the precursor material is 1-2 μm.

8. The method for preparing an N-doped graphene-coated silicon-based negative electrode material according to claim 1, characterized in that: In step (5), the process conditions of the high-speed sand mill are: motor power 3.2-4kW.

9. The method for preparing an N-doped graphene-coated silicon-based negative electrode material according to claim 1, characterized in that: In step (6), the process conditions for spray drying are: the inlet air temperature of the spray drying tower is 230-270°C, the outlet air temperature is 130-180°C, and the air flow is 2-8m 3 / min.

10. An N-doped graphene-coated silicon-based negative electrode material prepared by the method for preparing an N-doped graphene-coated silicon-based negative electrode material according to any one of claims 1 to 9.

Citation Information

Cited By

  • Carbon nanofiber conductive agent-based micron silicon carbon negative electrode and lithium battery application thereof

    CN120834149A